Assessing the level of digital technology use and readiness among micro-entrepreneurs from low-income backgrounds - Ishak, Suraiya; Che Omar, Ahmad Raflis; Tahir, Zurinah; Hamdan, Hamdino (IPMEDIA SDN BHD, 2025)
The rapid advancement of digital technology has significantly increased the importance of using digital tools in business management and marketing practices. To remain competitive in a dynamic market environment, it is essential for today's entrepreneurs to develop readiness in terms of skills, cognitive capacity, and technological tools to adopt digital technologies. This assumption is equally relevant to the growth and sustainability of micro-entrepreneurs from low-income backgrounds, particularly those receiving business assistance. Guided by the Technology Acceptance Model (TAM), this study assesses the level of adoption of digital technology and readiness among micro-entrepreneurs from this group. TAM is a widely used model for how users come to accept and use new technology, focusing on individual internal motivational factors, such as perceived usefulness and ease of use. A survey methodology was employed to collect the necessary data. The participants were micro-entrepreneurs classified as poor and needy who had received business capital support from the Negeri Sembilan Islamic Religious Council, funded through zakat-based resources. The findings indicate that the usage of digital technology is at a moderate level, while the readiness to adopt it is relatively high, with mean values of 3.578 and 4.023, respectively. ANOVA analysis reveals that skills readiness (p = 0.022, p < 0.05) and cognitive readiness (p = 0.04, p < 0.05) are significantly associated with the extent of digital technology utilization. The results indicate that the possession of relevant skills and a positive mindset regarding the benefits of digital technology play a key role in determining its usage in business operations. These results highlight the need for targeted training programs aimed at enhancing digital competencies among low-income entrepreneurs. Strengthening these capacities is essential to support business sustainability and growth. This study aligns with the first Sustainable Development Goal (SDG) on poverty eradication, emphasizing the role of zakat optimization through productive distribution and the integration of modern technologies